Dirac neutrinos in an SU(2) left-right symmetric model - Díaz Chávez, Henry José (2022)
It is known in the Standard Model of particle physics that the parity symmetry is violated (left- right asymmetry of fermions) in the weak interaction, consequently, neutrinos are considered as particles not massive, however, according to experimental facts, like in the case of neutrino oscillation, they must have mass. For this reason, one way to correct this asymmetry is to extend the gauge group SU (3)C SU (2)L U (1)Y to a group where the left and right fields are transformed in the same way, these models are called left-right symmetric models, where due to the presence of the right fields of the neutrinos these can gain mass. This work proposes a left-right symmetric model, where the scalar sector consisting of two doubles and two bidoublets (could include more bidoublets), in which neutrinos remain as Dirac fermions, like the charge leptons and quarks, in all orders in perturbation theory. However, only with two bidoublets the neutrino masses still need a fine-tuning, this would not be the case when a third bidoublet is added to our scalar sector. One of the scalar doublets may be regarded as inert, because the left-right symmetry forbids it to couple with the known fermions.